Balinese Mothers Developmental Timetables For Young Children - Phoebe Dauz Williams; Soetjiningsih Soetjiningsih (Paediatrica Indonesiana, 1992)
Cultures differ from one another in the types of competence that adults encourage in children, the age at which they expect a given skill to be acquired, and the level of proficiency they want children to achieve. The concept of developmental timetables refers to the ages at which parents expect skills to appear in children. The purpose of the study was to investigate the developmental timetables of rural and urban mothers in Bali, Indonesia, and the extent to which mother’s teach children various skills before Kindergarten age. The total sample was 200, 100 rural mothers and 100 urban mothers in the regency of Badung. Mothers responded to a structured questionnaire which was read to them aloud by trained interviewers who then recorded the responses. All the mothers had children between 4-6 years old; equal numbers of male and female children were included, and the entire economic and educational ranges were represented. Results showed that urban and rural mothers differed in their age expectations of children's development. Rural mothers reported wider age ranges as well as older mean ages of skill acquisition by children compared to urban mothers. Furthermore, specific caregiving activities, were performed earlier by urban mothers compared to rural mothers. However, reading the first book to the child was both quite late for urban and rural mothers. The implications of the findings to child development were discussed.